1979
DOI: 10.1021/bi00578a026
|View full text |Cite
|
Sign up to set email alerts
|

Lipid lateral diffusion by pulsed nuclear magnetic resonance

Abstract: The temperature and hydration dependences of lipid lateral diffusion in model membrane-D20 multilayers of dipalmitoyl (DPL), dimyristoyl (DML), dilauryl (DLL), and egg yolk (EYPC) lecithins were measured by using pulsed gradient proton NMR spin-echo techniques. Oriented samples were used to minimize anisotropic dipolar interactions and permit formation of a spin-echo. A general discussion of the technique and of the possible errors is included. Significantly lipid lateral diffusion is hydration dependent over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
81
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(109 citation statements)
references
References 57 publications
28
81
0
Order By: Relevance
“…Further, a variety of experimental methods report significantly different values for the diffusion coefficient. Experimental studies using pulsed field gradient nuclear magnetic resonance, 46 single particle tracking, 47 fluorescence recovery after photobleaching, 48 or from fluorescence correlation spectroscopy 49 report values within 0.5 × 10 −7 cm 2 /s and 1 × 10 −7 cm 2 /s. Neutron scattering experiments, operating in the picosecond range, produce diffusion coefficients significantly higher, 7,8,50 in the range of 1 to 10 × 10 −7 cm 2 /s.…”
Section: Mechanisms Of Lipid Diffusionmentioning
confidence: 99%
“…Further, a variety of experimental methods report significantly different values for the diffusion coefficient. Experimental studies using pulsed field gradient nuclear magnetic resonance, 46 single particle tracking, 47 fluorescence recovery after photobleaching, 48 or from fluorescence correlation spectroscopy 49 report values within 0.5 × 10 −7 cm 2 /s and 1 × 10 −7 cm 2 /s. Neutron scattering experiments, operating in the picosecond range, produce diffusion coefficients significantly higher, 7,8,50 in the range of 1 to 10 × 10 −7 cm 2 /s.…”
Section: Mechanisms Of Lipid Diffusionmentioning
confidence: 99%
“…Translational molecular mobility in model membranes has been studied by various physical methods including electron spin resonance (ESR), fluorescence recovery after photobleaching (FRAP) and others [1][2][3][4]. Pulsed field gradient nuclear magnetic resonance (PFG NMR) spectroscopy has been used extensively for diffusion measurements for many years [5][6][7][8][9] and is one of the most attractive methods for investigations of molecular transport in lipid membranes as no perturbing labeling of the molecules under study is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Translational diffusion of water and lipids in lamellar liquid crystalline phases has been studied by PFG NMR in a number of investigations [5][6][7][8][9][10][11][12]. For those studies NMR technique of the sample orientation at the magic angle has been applied, because for molecules with large dipole couplings, such as amphiphilic molecules in lamellar liquid crystalline phases, the NMR method removing the dipole interaction becomes necessary.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Thompson and Axelrod reported that a 30% cholesterol depletion of human erythrocyte membrane was not accompanied by a significant reduction of lipid lateral diffusion at 37 °C (Thompson and Axelrod 1980). In lipid bilayers comprising a single phospholipid species and cholesterol, no investigation has demonstrated that cholesterol enrichment is sufficient to account for, at a quantitative level, the difference in physical properties observed in RBC between the two leaflets; a factor of about 2 is the maximum effect reported (Devaux and McConnell 1972;Wu et al 1977;Rubenstein et al 1979;Kuo and Wade 1979;Lindbloom et al 1981;Shin and Freed 1989).…”
Section: Introductionmentioning
confidence: 99%